Fonologi: Karakteristik Huruf Hijaiyyah dan Makna Kosakata Bahasa Arab - Fauzi, Maira (Lembaga Penelitian dan Pengabdian pada Masyarakat, Institut Agama Islam Negeri (IAIN) Kerinci, Jambi, 2023)
This article aims to explore the characteristics of hijaiyyah letters and their influence on the meaning of Arabic vocabulary. The data analysis in this research is content analysis with a phonological approach with qualitative research methods. The results show that Articulation (makharijul huruf) is very important in pronunciation because pronunciation errors can affect a sound and meaning. This research is expected to provide a more in-depth view for teachers, students, and researchers about the importance of phonology and its influence on vocabulary meaning, and can be the basis for further empirical research